A new bamboo-feeding species of the leafhopper genus Neurotettix Matsumura (Hemiptera, Cicadellidae, Deltocephalinae) from China - Wang, Jing; Yang, Lin; Chen, Xiang-Sheng (Zootaxa, 2021)
A new bamboo-feeding species of the leafhopper genus Neurotettix Matsumura (Hemiptera, Cicadellidae, Deltocephalinae), Neurotettix spinas sp. nov. is described and illustrated from Guizhou Province, China. A checklist and a key to known species of the genus are also given, and a map showing the geographic distributions of all species of Neurotettix is also provided. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).